Hubungan Dukungan Orangtua dan Konsep Diri dengan Kepercayaan Diri Siswa - Rebekka Saormauli Simorangkir; M. Abrar Parinduri; Nurani Nurani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine whether there is a relationship between parental support and self-concept on self-confidence. The research method is quantitative descriptive correlative type. The research population is the XII grade students of SMA Negeri 1 Habinsaran. The sampling technique used is the Proportional Random Sampling technique with the number of selected samples as many as 57 people. The results obtained indicate that (1) there is a significant relationship between parental support and student self-confidence as indicated by the coefficient rx1y = 0.352 and p = 0.001, namely p < 0.05; (2) there is a significant relationship between students' self-concept and students' self-confidence, which is indicated by the coefficient rx2y = 0.177 and p = 0.008, namely p<0.05; (3) there is a significant relationship between parental support and students' self-concept with students' self-confidence as indicated by the coefficient F = 4.311 and R (regression coefficient) = 0.371 while R2 = 0.138 with p < 0.05 and Std. Error of the Estimate 12.25409 so that the conclusion produces a significant positive relationship between the three variables analyzed).